2019
DOI: 10.3390/nano9081070
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Microstructure and Mechanical Properties of Aluminum-Matrix Reinforced-Graphene Nanosheet Composites Fabricated by Mechanical Milling and Equal-Channel Angular Pressing

Abstract: Layered-graphene reinforced-metal matrix nanocomposites with excellent mechanical properties and low density are a new class of advanced materials for a broad range of applications. A facile three-step approach based on ultra-sonication for dispersion of graphene nanosheets (GNSs), ball milling for Al-powder mixing with different weight percentages of GNSs, and equal-channel angular pressing for powders’ consolidation at 200 °C was applied for nanocomposite fabrication. The Raman analysis revealed that the GNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“…When other studies on ECAP process were examined, it was seen that the microstructure images taken as a result of the forming process showed similar characteristics and orientations with the current study. [60][61][62] Figures 7(e) and (f) show SEM images of the sample subjected to more than one ECAP processes. It can be asserted that there was a decrease in the grain sizes with the increasing ECAP number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When other studies on ECAP process were examined, it was seen that the microstructure images taken as a result of the forming process showed similar characteristics and orientations with the current study. [60][61][62] Figures 7(e) and (f) show SEM images of the sample subjected to more than one ECAP processes. It can be asserted that there was a decrease in the grain sizes with the increasing ECAP number.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the literature. 60,[63][64][65][66] It was observed that there was a serious increase in the hardness of the ECAPprocessed samples. While microhardness value of the sample N0 in Figure 8(a) was 34.6 HV, an increase of 33% was observed when the same sample was subjected to ECAP process.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from polymers, hybrid fillers can potentially escalate the effectivity of the fillers' role throughout the matrix, more than individual h-BN sheets. The combination of different thermal conductive fillers like CNT [35,71], Graphene [72][73][74], Graphite [27,75], ZnO [76], Al 2 O 3 [77], and so on, with h-BN, leads to a synergetic effect in the TC performances among counterparts [68]. As an example, a promising hybrid nanocomposite of in-situ grown CNT on BNNSs embedded in epoxy resin exhibited a 615% and 380% TC performance improvement for the cross-plane direction compared with pure epoxy and BNNSs/epoxy composite, respectively.…”
Section: H-bn Within Hybrid Filler Configurationsmentioning
confidence: 99%
“…[46] Increased defect ratio of the 3% and 5% GNP samples can be attributed to higher disordering of the GNP sheets due to an increased number of collisions between stainless-steel balls and the GNP resulting from additional quantity of GNP. [47] Thus, it appears that the advancements of defects arise from increased quantity of GNP. However, despite the increment in I D /I G ratio for all three samples, the ratio less than 1 indicated the less defects and good quality of GNP deposition.…”
Section: Characterization Of Ball Milled þ Sintered Gnp-cu Coatingsmentioning
confidence: 99%